SUSCEPTIBILITY PATTERN OF METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS BACTERIA IN DR. SOETOMO GENERAL ACADEMIC HOSPITAL SURABAYA - Sacharissa Zerlina Tsarwah Thirafi; Rosantia Sarassari; Bramantono Bramantono; Kuntaman Kuntaman (Universitas Airlangga, 2022)
Background: Methicillin-resistant Staphylococcus aureus (MRSA), Gram-positive bacteria causing infection in hospital-acquired infection, has increased worldwide, including in Indonesia. Currently, the updated data on MRSA in Indonesia is limited. Purpose: This study aims to explore the prevalence and susceptibility pattern of MRSA in Dr. Soetomo General Academic Hospital Surabaya, Indonesia. Methods: This study was a descriptive-analytic study with a retrospective design. All clinical isolates of Methicillin-sensitive Staphylococcus aureus (MSSA) and MRSA from January to December 2017 were included. All inpatients included one MSSA or MRSA, and colonized bacteria were excluded. Data were analyzed using Chi-Square or Fisher’s Exact Test. Results: A total of 503 Staphylococcus aureus isolates were identified, of which 126 (25.05%) were MRSA. The highest prevalence of MRSA was from pus, wound swab, and tissue, 59 (28.37%) from 333, and the highest prevalence of the ward was in the intensive care unit (50%). MRSA were highly sensitive to daptomycin (n=95/95; 100%), linezolid (n=123/125; 98.40%), vancomycin (n=120/125; 96.00%), nitrofurantoin (n=43/45; 95.56%), quinupristin-dalfopristin (n=112/121; 92.56%), fosfomycin (n=87/97; 89.69%), and moxifloxacin (n=104/117; 88.89%). The susceptibility of the other antibiotics such as rifampicin, clindamycin, erythromycin, chloramphenicol, cotrimoxazole, levofloxacin, gentamicin, and tetracycline was less than 80%. Conclusion: The prevalence of MRSA among hospitalized patients in Dr. Soetomo General Academic Hospital, Surabaya, is 25.05% and tends to decrease from January to December 2017. Most MRSA was sensitive/intermediate to daptomycin, linezolid, vancomycin, nitrofurantoin, quinupristin-dalfopristin, fosfomycin, and moxifloxacin.